DAILY HOLTER ECG MONITORING IN THE DIAGNOSTIC ALGORITHM OF HEART RHYTHM AND CONDUCTION DISORDERS IN CHILDREN AND ADOLESCENTS - Т. Крючко; С. Танянська; Ю. Рубан; М. Олійніченко; С. Литус (Bukovynian State Medical University, 2024)
Recent years have seen an increase in the prevalence of cardiac arrhythmias and conduction disorders in children, which are not always diagnosed in time. In order to verify the nature of arrhythmias in pediatrics as well as in therapy, an accessible and informative method of daily Holter ECG monitoring (DHECGM) is widely used. Aim of the study was to assess the practical value of DHECGM in the algorithm for diagnosing heart rhythm and conduction disorders in pediatric patients. Materials and Methods: Analysis of DHECGM was performed in 48 children who were hospitalized in the pediatric department of the Specialized Pediatric Care Center (SPCC) of the Poltava Regional Clinical Hospital (PRCH) in 2022-2023. Research results. Sinus tachyarrhythmia or bradyarrhythmia, wandering atrial pacemaker was detected in half of the patients studied. Supraventricular and/or ventricular extrasystoles were detected in 87.5 % of children. Bi-, tri- and quadrigeminy were observed in 14 (27.1 %) of the patients. First or second degree sinoatrial block was observed in 25 % of patients. Atrioventricular block of 1st or 2nd degree (Mobitz type) with Wenkenbach- Samoilov periods was observed in 8 patients (16.6 %). Combined rhythm and conduction disturbances were observed in 82.3 % of the children studied. The article is illustrated by clinical cases of cardiac rhythm and conduction disorders in children of diff erent ages. Conclusions: DHECGM has broad capabilities for diagnosing cardiac rhythm and conduction abnormalities, allowing early detection of arrhythmias in pediatric patients and providing personalized recommendations.